How Entrepreneurial Agility Drives International Performance in Commodity-Trading SMEs - Junaedy, Agoes; Kaihatu, Thomas Stefanus; Tambunan, Damelina Basauli (Jurnal Minds: Manajemen Ide dan Inspirasi, 2026)
This study examines entrepreneurial agility as a mediating mechanism linking entrepreneurial orientation and innovation capability to international business performance among Indonesian commodity-trading SMEs. This study contributes to international entrepreneurship literature by reconceptualizing innovation capability, rather than entrepreneurial orientation, as the primary foundation of entrepreneurial agility in emerging-market SMEs. Drawing on effectuation theory and business model innovation theory, data from 300 export-oriented SMEs were analyzed using PLS-SEM. The findings reveal that innovation capability significantly strengthens entrepreneurial agility and indirectly enhances international business performance through partial mediation. In contrast, entrepreneurial orientation primarily influences performance through direct pathways rather than agility formation, challenging dominant assumptions regarding the adaptive role of entrepreneurial orientation. These findings suggest that SMEs operating in volatile international markets should prioritize innovation-driven capability development to strengthen agility and sustain international competitiveness.